If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + -9 + -4x + 9 = 0 Reorder the terms: -9 + 9 + 15x + -4x = 0 Combine like terms: -9 + 9 = 0 0 + 15x + -4x = 0 15x + -4x = 0 Combine like terms: 15x + -4x = 11x 11x = 0 Solving 11x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '11'. x = 0 Simplifying x = 0
| n^2+n=45 | | 9l-22=23+4l | | X=-8+15 | | 4m+6=17 | | 13w+39= | | y-2=.666x-27 | | 3.3x-4.2=-0.4 | | y-(-5)=-11 | | 11y-7.5-7y=2 | | C=3.50p+550 | | 48+12s= | | 8(e+6)=3(e+33) | | -34+x+36=32 | | (2x+5)=(3x-8) | | 4(2b+-6)+11=8b+-13 | | 1.5y-7=0.5y | | 5+x+x=2x+6 | | y-7=-.5x-(-6) | | 4a+10=8a+2 | | 11x-(6x-5)=110 | | 3x-4y+5z=-1 | | (2x+10)=(7y-8) | | 2x+-8y=-4 | | 4a-10=8a+2 | | -(-2)+10(-6)= | | 10-6x=4+46 | | 10n-10=4+12(n+11) | | -2(-8q+7)+5q= | | 21=4X-9X | | 3x^4+31x^3+56x^2=0 | | -b+3b-2=2-4b+12 | | 5(5x+1)+4=26x+2 |